Quenching in Arabidopsis thaliana Mutants Lacking Monomeric Antenna Proteins of Photosystem II - Miloslavina, Yuliya (American Society for Biochemistry and Molecular Biology, 2011)
The minor light-harvesting complexes CP24, CP26, and CP29 have been proposed to play a key role in the zeaxanthin (Zx)-dependent high light-induced regulation (NPQ) of excitation energy in higher plants. To characterize the detailed roles of these minor complexes in NPQ and to determine their specific quenching effects we have studied the ultrafast fluorescence kinetics in knockout (ko) mutants koCP26, koCP29, and the double mutant koCP24/CP26. The data provide detailed insight into the quenching processes and the reorganization of the Photosystem (PS) II supercomplex under quenching conditions. All genotypes showed two NPQ quenching sites. Quenching site Q1 is formed by a light-induced functional detachment of parts of the PSII supercomplex and a pronounced quenching of the detached antenna parts. The antenna remaining bound to the PSII core was also quenched substantially in all genotypes under NPQ conditions (quenching site Q2) as compared with the dark-adapted state. The latter quenching was about equally strong in koCP26 and the koCP24/CP26 mutants as in the WT. Q2 quenching was substantially reduced, however, in koCP29 mutants suggesting a key role for CP29 in the total NPQ. The observed quenching effects in the knockout mutants are complicated by the fact that other minor antenna complexes do compensate in part for the lack of the CP24 and/or CP29 complexes. Their lack also causes some LHCII dissociation already in the dark.